Management of common risk during construction stage on low-cost apartment housing project in Selangor / Mohd Fadil Md Noh - Md Noh, Mohd Fadil (Faculty of Architecture, Planning and Surveying, 2009)
Risk was one its state that incident not able identified accurately. Its existences always referred will bring negative impact such as destruction or loss. In construction works in housing project, risk existence always associated with project delay and cost increase. However, this negative impacts not something inevitable or minimized. Contractor as responsible party to carry construction works should be prepared to deal construction risks to ensure construction project success. Nevertheless, housing developer are also accountable to manage risk effectively and to minimize delay and avoid project abandonment. Purpose of the study is to generally identify common construction risk, generally analyze the level of risk and finally generally identify available methods to reduce or mitigate the risks during construction stage. This study focused on the low-cost apartment housing project, whether on project that has been complete or still under construction which implemented by housing developer in Selangor Darul Ehsan area. The study shall include related literature review, followed with form distribution questionnaire to housing developer involved in low-cost apartment project and through interview session with professional staff. While for analysis of data, the scale of measurement is likert scale and the data is presented in average index mean formula, schedule, bar graph, reporting, discussion and description. The types of risk identified are classified to several category namely physical risks, design risk, construction risk and risk on environment. Risk level of each category is subsequently presented in schedule and graph. The results indicated that the major risk factors occur in construction project is construction risk. Where two type of risk found in construction risk category is at levels major namely prices increase on materials and equipment, and poor supply of material. Lastly, there are four (4) methods that can be used to reduce on avoid risk in low-cost apartment project which are risk reduction, risk avoidance, risk transfer and risk retention. Finally the result indicated that, risk reduction is the best methods, most effective and greatest serves to overcome risk which occurred.